Optimization Of Sodium Croscarmellose And Sodium Starch Glycolate In Orally Disintegrating Tablets (Odt) Acetosal - Endang Diyah Ikasari (Media Farmasi Indonesia, 2025)
Acetosal is a drug that is included in the NSAID class which has anticoagulant properties. Acetosal has low bioavailability due to first-pass effect metabolism, so it is formulated in ODT form to increase the bioavailability of acetosal. This research aims to determine the effect of croscarmellose sodium and sodium starch glycolate concentrations as superdisintegrants on the physical characteristics of acetosal ODT and to determine the concentrations of croscarmellose sodium and sodium starch glycolate as superdisintegrants that produce acetosal ODT with optimum physical characteristics. The ratio formula for CCS and SSG obtained from design expert 10.0.1 using the simplex lattice design method, namely FI (0:6); FII (3:3); FIII (6:0); FIV (4.5:1.5); FV (6:0); FVI (0:6); FVII (3:3); FVIII (1.5:4.5). Based on the research results, the optimum ODT formula for acetosal was obtained with a concentration of CCS 1.232% and SSG glycolate of 4.768%. The optimum formula test results obtained a flow rate of 19.706 grams/second, MC 2.574%, compressibility 24.00%, hardness 3.70 kg, friability 0.668%, disintegration time 40.574 seconds, wetting time 46.002 seconds, and dissolution 95.142%. Based on the t-test between theoretical and experimental results, the results show that the results are not significantly different so they are said to be valid.